Effects of posture and anatomical location on inter-recti distance measured using ultrasound imaging in parous women. (April 2018) - Gillard, S.; Ryan, C.G.; Stokes, M.; Warner, M.; Dixon, J.
Abstract: Study design: Cross-sectional repeated measures. Objectives: To quantify the effects of posture and measurement site on the inter-recti distance (IRD) and investigate the reliability of IRD measurement using ultrasound imaging in different postures. Background: The linea alba connects the rectus abdominis muscles anteriorly and the width is known as the IRD. The IRD is usually measured in crook-lying and is the primary outcome measure to assess for a divarication of recti abdominis (DRA). The effects of posture and measurement site on the IRD have not been investigated. Methods: Ultrasound imaging was used to measure IRD in 41 women ≥8 weeks postpartum. The IRD was measured at three sites (superior-umbilicus, umbilicus and inferior-umbilicus), in three postures (crook-lying, sitting and standing), and repeated one-week later. The effects of posture and site were investigated using one-way ANOVAs. Reliability was analysed using Intraclass correlation coefficients (ICCs), Bland Altman analyses, standard error of measurement and minimal detectable change. Results: The IRD was wider when standing vs. lying at both the superior-umbilicus and umbilicus by 0.30 cm (95% CI 0.21 to 0.39) and 0.20 cm (0.11–0.30) respectively (p < 0.001). Measurements at the inferior-umbilicus were, on average, 1.6 and 2.1 cm narrower than superior-umbilicus and umbilicus sites, respectively (p < 0.001). There was high intra-rater reliability within-session (ICC3.3 ) and between-session (ICC3.1 ) at all sites measured. Conclusion: The IRD can be measured reliably at all sites and postures. The IRD is wider at superior-umbilicus and umbilicus when upright compared with lying. There is a difference in IRD between all sites measured. Highlights: The clinical relevance of measuring the IRD in sitting and standing is examined. Standardisation of the exact location to measure IRD is proposed. Ultrasound imaging to measure IRD in sitting and standing is investigated.